Synthesis, characterization and photophysical studies of novel pyrene labeled ruthenium (II) trisbipyridine complex cored dendrimers. (2nd September 2016) - Vonlanthen, Mireille; Cevallos-Vallejo, Amanda; Aguilar-Ortíz, Edgar; Ruiu, Andrea; Porcu, Pasquale; Rivera, Ernesto
Abstract: Two new bipyridine ligands containing, respectively, two and four pyrene units were prepared. The obtained compounds were employed to synthesize new pyrene labeled ruthenium (II) trisbipyridine complex as well as a pyrene labeled ruthenium (II) trisbipyridine cored dendrimer. The obtained bipyridine ligands and the ruthenium complexes were characterized by NMR spectroscopy and MALDI-TOF mass spectroscopy. The optical and photophysical properties of the luminescent macromolecules were studied by absorption and fluorescence spectroscopy. It was noticed that the absorption spectra of the obtained complexes correspond to the sum of the absorption spectra of their components, which indicates a lack of interaction in the ground state. Efficient energy transfer was observed from pyrene units to the metal complex core resulting in the observation of the characteristic ruthenium bipyridine emission band upon excitation at the pyrene absorption wavelength. Moreover, efficient protection to oxygen quenching was remarked in the first generation dendrimer. Graphical abstract: Highlights: Pyrene-labeled ruthenium bipyridine-cored dendrimers were synthesized. No interaction between pyrene and ruthenium units was present in the ground state. Efficient energy transfer from pyrene units to the ruthenium complex was observed. Protection from oxygen quenching was effective in the second generation complex.